2019
DOI: 10.1039/c9tb01196j
|View full text |Cite
|
Sign up to set email alerts
|

D–A polymers for fluorescence/photoacoustic imaging and characterization of their photothermal properties

Abstract: Two D–A polymers with good NIR-II fluorescence, photoacoustic and photothermal properties were designed and synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…[41] Whereas, Langmuir isotherm model is usually associated with ionic substrates (metal cations) adsorption with weak competition from the solvent molecules. [42] For lower concentration, the Langmuir isotherm model has been found to be more satisfactory, while the adsorption index (0.1 < 1/n < 0.5) of Freundlich isotherm model means that adsorption intensity is favorable at high concentrations. [43] Therefore, it can be concluded that the high adsorption capacity of AMP-PAN towards Rb(I) ion.…”
Section: Adsorption Isothermmentioning
confidence: 96%
“…[41] Whereas, Langmuir isotherm model is usually associated with ionic substrates (metal cations) adsorption with weak competition from the solvent molecules. [42] For lower concentration, the Langmuir isotherm model has been found to be more satisfactory, while the adsorption index (0.1 < 1/n < 0.5) of Freundlich isotherm model means that adsorption intensity is favorable at high concentrations. [43] Therefore, it can be concluded that the high adsorption capacity of AMP-PAN towards Rb(I) ion.…”
Section: Adsorption Isothermmentioning
confidence: 96%
“…Dyes such as melanin [33,34] and porphyrin derivatives [35,36] react with other polymers to improve the PA signal. Polymers that have been employed as contrast agents include protein [37,38], phospholipid [39] and biodegradable polymers [40,41]. These polymers can be used in the form of NPs via precipitation and dispersion, which leads to self-assembly, and in the form of dots.…”
Section: Organic Pa Contrast Agentsmentioning
confidence: 99%
“…Zhu et al developed contrast agent NPs using 1,2-distearoyl-sn-glycero-3-phosphoeth anolamine-N-[methoxy(polyethylene glycol)-2000] (DSPE-mPEG2000), octyl 4,6-dibromoth ieno [3,4-b]thiophene-2-carboxylate (TT) and 3,6-bis(5-bromothiophen-2-yl)-2,5-bis(2-ethylh exyl) pyrrolo [3,4-c]pyrrole-1,4(2H,5H)-dione (DPP) [39]. They conjugated DSPE-mPEG2000 with TT or DPP to form P-TT and P-DPP, respectively.…”
Section: Organic Pa Contrast Agentsmentioning
confidence: 99%
“…31 SWIR°uorescent probes are expected to have good biocompatibility, high°uorescence quantum e±ciency, and adjustable excitation and emission wavelengths in the short-wave infrared region. 32,33 Under these considerations, conjugated polymers with donor-acceptor (D-A) structure are ideal materials for constructing short-wave infrared°u orescent probes. Moreover, their optical properties could be easily adjusted by changing the main backbone or side chain structure.…”
Section: Introductionmentioning
confidence: 99%